The Transmission of Knowledge from the Islamic World to Europe during the Renaissance: A Bridge to the Modern Era - Hoerotunnisa; Nanat Fatah Natsir; Erni Haryati; Moch Ardia Putra; Hani Rolis (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This paper reviews the process of knowledge transmission from the Islamic world to Europe during the Renaissance, which served as a vital bridge to the modern era. Using a historical and multidisciplinary analysis approach, the article highlights the significant contributions of Islamic civilization in establishing the foundations of modern science. The findings show that Muslim scholars, through the translation and development of classical Greek works, made significant contributions in philosophy, science, mathematics, and medicine. The study also underscores the primary routes of transmission, including Andalusia, Sicily, and the Crusades, which served as mediums for cultural and intellectual exchange between East and West. This article emphasizes the importance of inter-civilizational dialogue in fostering inclusive and progressive knowledge.